2016
DOI: 10.3892/br.2016.817
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D improves immune function in immunosuppressant mice induced by glucocorticoid

Abstract: Vitamin D is an essential fat-soluble vitamin with multiple functions. Vitamin D receptor has been shown to be expressed in several types of immune cells suggesting vitamin D may have immune regulatory roles. Vitamin D insufficiency has been suggested to increase the risk of autoimmune diseases. However, little is known regarding its immunomodulatory effects in the condition of immune suppression. The aim of the present study was to investigate the regulatory effects of vitamin D on immune function in immunosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…In many species, including chickens, mice, and humans, CD4+:CD8+ cell ratio is an indicator of immune competence [ 47 , 50 , 51 ]. In general, a CD4+:CD8+ cell ration that is higher than 1, reflecting a higher percentage of CD4+ cells relative to CD8+ cells, is observed in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In many species, including chickens, mice, and humans, CD4+:CD8+ cell ratio is an indicator of immune competence [ 47 , 50 , 51 ]. In general, a CD4+:CD8+ cell ration that is higher than 1, reflecting a higher percentage of CD4+ cells relative to CD8+ cells, is observed in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Calcitriol was reported to induce cellular arrest, trigger apoptotic signaling, and regulate reactive oxidative stress (ROS) and inflammation to affect cancer development and growth. In addition, calcitriol was shown to augment the tumor inhibition induced by anticancer modalities, including RT ( 15 , 16 ). Calcitriol shows actions in several pathways, including the p38-MAPK, IL-6, TGF-β1 and NF-κB signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly synthesized in the liver and widely distributed in various body fluids (such as plasma, cerebrospinal fluid, semen, saliva, and breast milk) (7,8). It is also expressed in immune cells such as T lymphocytes, monocytes, macrophages, and dendritic cells (9), as well as in articular chondrocytes and synoviocytes at the site of RA injury (10). Our previous study showed that VDBP was significantly reduced in the synovial tissue of RA patients (11).…”
Section: Introductionmentioning
confidence: 99%